1990
DOI: 10.1557/jmr.1990.2133
|View full text |Cite
|
Sign up to set email alerts
|

Silicide precipitation and silicon crystallization in nickel implanted amorphous silicon thin films

Abstract: The nucleation and growth kinetics of NiSi2 precipitation in amorphous silicon thin films ion implanted with nickel was investigated using scanning transmission electron microscopy. It was found that the nucleation rate could be approximately described by a delta function at time t = 0 when the films were annealed between 325 and 400 °C. The growth kinetics of the precipitates at these temperatures were described by r ∝ tn, where r was the average radius and n was about 1/3. This behavior is consistent with mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(28 citation statements)
references
References 6 publications
0
27
0
Order By: Relevance
“…al. studied the mechanism of Ni silicide mediated crystallization with in situ TEM observation [12][13][14]. They reported that Ni reacts with Si to form NiSi 2 precipitates and crystalline Si nucleates at the surface of the NiSi 2 precipitates.…”
Section: Resultsmentioning
confidence: 99%
“…al. studied the mechanism of Ni silicide mediated crystallization with in situ TEM observation [12][13][14]. They reported that Ni reacts with Si to form NiSi 2 precipitates and crystalline Si nucleates at the surface of the NiSi 2 precipitates.…”
Section: Resultsmentioning
confidence: 99%
“…The nucleation temperature of a-Si is decreased by the addition of a catalytic metal; the process is referred to as MILC and catalyst-assisted SPC (Kawatsu et al, 1990;Cammarata & Thompson, 1990;Takayama et al, 2000). Although metals such as Al, Mo, Ni, Pd, and Ti have been applied to cause MILC, Ni is the most frequently used catalyst.…”
Section: Metal-induced Lateral Crystallizationmentioning
confidence: 99%
“…5,6 Recently, a Ni implantation technique combined with thermal annealing has also been employed to investigate the formation behavior of NiSi 2 . 7,8 For example, Cammarata et al, 9,10 investigating the formation behavior of NiSi 2 in Ni-implanted, amorphous-Si thin films, showed that crystalline NiSi 2 precipitates are formed in the amorphous-Si films during thermal annealing. It was further shown that the nucleation rate of NiSi 2 could be expressed by a delta function at t ϭ 0 for temperatures of 325-400°C.…”
Section: Introductionmentioning
confidence: 99%